Different times? : archaeological and environmental data from intra-site and off-site sequences : proceeedings of the XVIII UISPP World Congress (4-9 June 2018, Paris, France). - Tsirtsoni, Zoï,; Kuzucuoǧlu, Catherine,; Nondédéo, Philippe,; Weller, Olivier, (Archaeopress Archaeology, 2020)
This title provides the proceedings from session II-8 of the XVIII UISPP Congress, Paris, 2018, questioning temporal correlations between intra-site and off-site data in archaeology-related contexts. The word 'site' describes here archaeological sites - usually settlements - where recent research has produced information on the duration and timing of human presence.